« Domestiquer » l’incertitude : Les sociétés d’État comme instrument d’adaptation aux changements économiques internationaux - Lacasse, François (Études internationales, 1983)
The author recalls briefly the recent growth (20 years) of the Government controlled enterprises in the market economies : relative weight multiplied by three and mostly, a very strong diversification of their activities. Because pressure front the international environment is exerted on the old industrial societies like Canada in order that they redeploy, this trend will continue. Adaptations are made difficult and politically costly by social rigidness. In this connection, Government controlled enterprises offer very clear advantages compared to the other means available (flexibility, discretion, existence capacity of the adapters and late-comers, dispersion of forums of conflict, cooptation of the elites, real and expected contributions to growth). The forces which hinder the privatization of the Government controlled enterprises, coming from the conservative parties, are impressive : economic and political costs, possibilities of de facto privatization, the interests of the Government controlled enterprises themselves and their allies. In short, it is very likely that this trend will go on. In the face of this, the amount of expert knowledge leaves much to be desired'; some of the main lines of research are dead ends. The author outlines some new directions which will allow research to really integrate the Government controlled enterprises in the economic predictions and policy making.